Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pengguna Jasa Penyewaan Baju Pengantin Studi Kasus Pada CV. Tini Suherlan Jakarta Selatan - Dinda Hanako Fadhilah W; Hartono Hartono; Hermansyah Hermansyah (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study was to analyze the effect of service quality and price on customer satisfaction at wedding dress rental service CV. Tini Suherlan, either partially or simultaneously.The research used quantitative research. The population in this study were all active customers of CV. Tini Suherlan in 2021. The data collection techniques in this study was a Likert Scale. The sampling techniques was the Roscoe formula with a sample of 30 people, and the data analysis techniques were validity tests, reliability tests, analysis of average respondents’ responses, descriptive analysis of variables, normality test, multicollinearity test, hypothesis test (correlation coefficient, multiple linier regression analysis, t test, F test and coefficient of determination test). The result showed that: 1) Based on the result of the t-test of the service quality variable, the tcount value was 1.491 with significance level of 0.000 > 0.05. This indicates that the dependent variable of service quality individually or partially has a significant and significant effect on customer satisfaction; 2) Based on the results of the t test, it is concluded that the price variable also highly influences customer satisfaction in addition to reliability in providing services to customers and good quality of goods. The value of tcount on the price variable was 0.692 with a significance value of 0.000 > 0.05. This indicates that the price individually or partially has a significant and significant effect on customer satisfaction; 3) Partial test results The F test showed that the service quality and price variables produce an Fcount value of 1.507 with a significance level of 0.000 > 0.05. These results indicate that the quality of service and price together or simultaneously have a significant effect on customer satisfaction.